EFFECTS OF COLUMN FAILURES ON THE INTERNAL FORCES OF ORTHOGONAL REINFORCED CONCRETE BUILDING FRAMES - Kaya, Nilay; Gurel, M. Arif; Erdogan, A. Sayil; Gumuscu, Mehmet; Pekgokgoz, R. Kadir (Pamukkale Univ, 2006)
In this study, the effects of column failures which may take place due to the special causes such as blast, vehicle impact, insufficient or deficient design, on the internal forces of orthogonal reinforced concrete building frames have been investigated. Calculations have been performed with SAP2000 structural analysis program, under static conditions. For a typical frame system, firstly, various column failure scenarios have been considered for uninfilled case and internal forces have been calculated and compared with those in the intact case. Then, similar calculations have been implemented for the case of presence of infill walls. The results of analyses have shown that the effects of column failures had condensed on the neighbor columns and beams of orthogonal frames on which the columns had been failed. Moreover, it has been determined that, while the bending moment capacities of the connected beams to the failed columns had exceeded in the bare frames, in the masonry infilled frames, walls give substantial support to the structural elements of the building, and capacities of the beams had not exceeded.
Keywords: Orthogonal RC building frames; Column failures; Internal forces; Masonry infill walls